How do emerging market SMEs utilize resources in the face of environmental uncertainty? - Yama Temouri; Kathy Shen; Vijay Pereira; Xuanli Xie (BRQ Business Research Quarterly, 2022)
Using the resource-based view of the firm, this article examines how different resources are used by small- and medium-sized enterprises (SMEs) in response to environmental uncertainty in an emerging market context. A survey was conducted involving 212 owners, CEOs, or managing directors of SMEs in the United Arab Emirates (UAE) to explore the drivers of firm growth strategies. Our empirical results show that higher environmental uncertainty, in terms of market and regulatory uncertainty, drives SMEs to pursue a more exploratory instead of an exploitative growth strategy. Our results also show that SMEs pursuing more of an exploratory growth strategy focus predominantly on intangible resources such as human capital and social capital while firms pursuing more of an exploitative growth strategy focus more on financial resources. The results from our study provide valuable insights for how managers can structure, bundle, and leverage different resources for developing their strategies based on their level of perceived environmental uncertainty. The policy implications from our study are that support for SMEs should be multi-faceted depending on the combination of uncertainty faced and type of strategy chosen by SMEs.
Keywords: M10; M19; M13; 650; exploitative strategy; explorative strategy; financial capital; human capital; resource-based view; SMEs; social capital; UAE